Breaking the limits of sharia product promotion: Socio-cultural trust and community perception in conventional vs sharia pawnshop adoption - Ardy Firman Syah (Journal of Socio-Cultural Sustainability and Resilience, 2026)
Background: Pawnshops serve as an important non-bank liquidity channel in Indonesia, yet sharia-compliant products remain less adopted than conventional pawning despite a Muslim-majority market. This study examines how sharia products can expand their promotional reach within a conventional-dominated ecosystem, focusing on competition between PT Pegadaian’s conventional and sharia service lines. Methods: Using a qualitative explanatory approach based on selected secondary sources (regulations, institutional reports, and prior studies), the analysis applies thematic coding and comparative interpretation. Findings: The findings show that conventional services maintain advantages in product variety, brand familiarity, and simpler cost perceptions. This study distinguishes itself from previous literature by integrating legal-economic analysis with consumer behavior and promotional dynamics to explain why sharia pawnshop products remain less adopted despite their ethical and religious advantages. Conclusion: It fills the gap in prior studies that separately examined sharia compliance or customer preferences by showing how communication asymmetry, fee perception, and institutional “lock-in” shape market competitiveness, while contributing a novel framework that reframes the rivalry between conventional and sharia pawnshops as a contest between institutional logic and communicative legitimacy. Novelty/Originality of this article: The originality of this study lies in its effort to bridge the gap in the existing literature, which often separates the aspect of Sharia compliance from consumers’ practical preferences